Drought-induced recruitment of specific root-associated bacteria enhances adaptation of alfalfa to drought stress - Fan, Wenqiang; Tang, Fang; Wang, Jiani; Dong, Jiaqi; Xing, Jing; Shi, Fengling (Frontiers in Microbiology, 2023)
Drought is a major abiotic stress that threatens crop production. Soil microbiomes are thought to play a role in enhancing plant adaptation to various stresses. However, it remains unclear whether soil microbiomes play a key role when plants are challenged by drought and whether different varieties are enriched with specific bacteria at the rhizosphere. In this study, we measured changes in growth phenotypes, physiological and biochemical characteristics of drought-tolerant alfalfa (AH) and drought-sensitive (QS) under sterilized and unsterilized soil conditions with adequate watering and with drought stress, and analyzed the rhizosphere bacterial community composition and changes using 16S rRNA high-throughput sequencing. We observed that the unsterilized treatment significantly improved the growth, and physiological and biochemical characteristics of alfalfa seedlings under drought stress compared to the sterilized treatment. Under drought stress, the fresh and dry weight of seedlings increased by 35.24%, 29.04% and 11.64%, 2.74% for unsterilized AH and QS, respectively, compared to sterilized treatments. The improvement was greater for AH than for QS. AH and QS recruited different rhizosphere bacteria when challenged by drought. Interestingly, under well-watered conditions, the AH rhizosphere was already rich in drought-tolerant bacterial communities, mainly Proteobacteria and Bacteroidetes, whereas these bacteria started to increase only when QS was subjected to drought. When drought stress was applied, AH was enriched with more drought-tolerant bacteria, mainly Acidobacteria, while the enrichment was weaker in QS rhizosphere. Therefore, the increase in drought tolerance of the drought-tolerant variety AH was greater than that of the drought-sensitive variety QS. Overall, this study confirmed the key role of drought-induced rhizosphere bacteria in improving the adaptation of alfalfa to drought stress, and clarified that this process is significantly related to the variety (genotype). The results of this study provide a basis for improving drought tolerance in alfalfa by regulating the rhizosphere microbiome.